Interaksi Antara Daya Tumbuh Benih dengan Pertumbuhan Tanaman Semangka (Citrullus lanatus (Thunb.) Matsum dan Nakai) Pada Pemupukan Organik dan Anorganik - Nazirwan Nazirwan; Anung Wahyudi (Politeknik Negeri Lampung., 2015)
The aim of this research to observe and analyze the ability to grow of watermelon seeds in organic and inorganic fertilizers. Observing and analyzing the interaction between the ability to grow of watermelon seeds with plant growth in organic and inorganic fertilizers. Recommend a combination of organic and inorganic fertilizers that provide maximum results. This research was conducted in field of State Polytechnic of Lampung on June until Agustus 2014. This research uses a randomized complete block design (RCBD) with treatment in the form of thiamethoxam, inorganic fertilizers and organic fertilizers, namely: P1 = 0% organic fertilizer + 100% inorganic fertilizer; P2 = 25% organic fertilizer + 75% inorganic fertilizer; P3 = 50% organic fertilizer + 50% inorganic fertilizer; P4 = 75% organic fertilizer + 25% inorganic fertilizer; P5 = 100% organic fertilizer + 0% inorganic fertilizer. Doses of inorganic fertilizers: Urea = 300 kg.ha-1, SP-36 = 200 kg.ha-1, KCl = 100 kg.ha-1. Organic fertilizer: manure (cow manure) = 20 tons.ha-1. Data were analyzed with analysis of variance and if there is a real different treatments followed by LSD test at 5% level. The results showed that organic and inorganic fertilizer application significantly affected fruit length and fruit weight, but did not significantly affect the ability to grow, main stem length and number of leaves. The length of the longest fruit found in the treatment of inorganic fertilizer application of 75% + 25% organic fertilizer (P2). While the weight of the heaviest fruit found in the treatment of organic fertilizer application of 100% (P5). The highest ability to grow plant found in the treatment of 100% inorganic fertilizer application (P1), treatment of inorganic fertilizer application 50% + 50% organic fertilizers (P3), P2 and P5 treatment. The longest length of main stem found in P5 treatment, while the highest number of leaves found in P2 treatment. Keywords: fertilization, organic, inorganic, watermelon